2021
DOI: 10.1007/s11357-020-00300-2
|View full text |Cite
|
Sign up to set email alerts
|

Level of the SARS-CoV-2 receptor ACE2 activity is highly elevated in old-aged patients with aortic stenosis: implications for ACE2 as a biomarker for the severity of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) has a high mortality in elderly patients with pre-existing cardiovascular diseases. The cellular receptor of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the angiotensin-converting enzyme 2 (ACE2), thereby implicating a link between cardiovascular diseases and SARS-CoV-2 susceptibility. Aortic stenosis (AS) represents a chronic inflammatory state with severe cardiovascular complications in the elderly, a prime condition for COVID-19 mortality. The circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…This observation motivated us for the investigation of the signaling processes mobilized by rRIC. Interestingly, rRIC largely reduced tissue ACE and ACE2 activities in comparison to those in the MI group, and hence our data support direct links between the dysregulation of tissue ACE and ACE2 activities and myocardial remodeling as has been also illustrated by previous results of our group and others [21][22][23][24][25]. The mechanism by which rRIC lead to the downregulation of cardiac ACE and ACE2 activities was not aimed in this study.…”
Section: Discussionsupporting
confidence: 89%
“…This observation motivated us for the investigation of the signaling processes mobilized by rRIC. Interestingly, rRIC largely reduced tissue ACE and ACE2 activities in comparison to those in the MI group, and hence our data support direct links between the dysregulation of tissue ACE and ACE2 activities and myocardial remodeling as has been also illustrated by previous results of our group and others [21][22][23][24][25]. The mechanism by which rRIC lead to the downregulation of cardiac ACE and ACE2 activities was not aimed in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Serum ACE2 levels in end-stage heart failure patients were about fourfold higher than those in hypertensive subjects and about twofold higher than those in heart failure patients of low NYHA classes [ 28 , 29 ]. Our previous studies revealed an inverse relationship between serum ACE2 activity and left ventricular ejection fraction in heart failure patients with reduced ejection fraction (HFrEF) and in patients with hypertension [ 28 , 29 , 39 ]. This proposed negative correlation between circulating ACE2 activity and left ventricular ejection function has been confirmed here, in a large cardiovascular patient population ranging from mild hypertensives to end-stage heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since angiotensin II is elevated during the heart failure condition, the activity of ADAM-17 is internally promoted by angiotensin II that is reported in several cardiac diseases, as a feedback system to sustain the ratio of angiotensin II/ACE2 expression [ 39 ]. The cleaved and shed sACE2 circulates in the plasma of patients with heart failure [ 53 ], aortic stenosis [ 54 , 55 ] and coronary artery disease (CAD) [ 56 ] and positively correlates with worsening disease prognosis. Of note, plasma sACE2 has been accounted as a highly ranked and independent determinant for cardiovascular mortality compared to other established cardiovascular risk factors [ 57 ].…”
Section: Sars-cov-2 and Its Receptors In Cardiac Pathophysiologymentioning
confidence: 99%